Municipal Building Codes and the Adoption of Solar Photovoltaics - Stefano Carattini; Béla Figge; Alexander Gordan; Andreas Löschel (Center for Economic Studies and ifo Institute (CESifo), 2022)
Conflicting societal goals can lead to national and local policies that are at odds with each other. National policies promoting the adoption of solar photovoltaics may be counteracted by local policies defining the aesthetics of the built environment. As solar photovoltaic energy approaches grid parity globally, non-pecuniary barriers to the adoption of this important renewable energy source become increasingly salient. Using a unique survey of municipalities regarding such building codes and administrative data on all solar installations in Germany, a leader in solar adoption, we document the impact that municipalities amending their building codes to restrict solar installations, often with an eye toward preserving the historical nature of the town, has on solar adoption. We find that municipalities that implement solar policies have 10.4 percent less solar photovoltaic capacity than municipalities in the control group. We confirm our results when applying spatial techniques and analyzing the impact of such policies on regulated areas within municipalities.
Keywords: D62; H77; Q48; Q58; R52; 330; building codes; solar photovoltaics; policy evaluation; NIMBY